2015
DOI: 10.1016/j.ydbio.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of folate metabolism in orofacial development and clefting

Abstract: Folate deficiency has been associated with numerous diseases and birth defects including orofacial defects. However, whether folate has a role in the face during early orofacial development has been unclear. The present study reveals that pharmacological and antisense oligonucleotide mediated inhibition of DHFR, an integral enzyme in the folate pathway, results in specific changes in the size and shape of the midface and embryonic mouth. Such defects are accompanied by a severe reduction in the muscle and cart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 63 publications
(96 reference statements)
1
51
0
Order By: Relevance
“…Longer exposure times often lead to severe effects where tissues separated from the face (n = 10; 1 experiment; not shown) and, therefore, were not assessed. We observed similar results when embryos were treated with chemicals shown to induce cell death in Xenopus (2% ethanol, Kot‐Leibovich and Fainsod, ; and methotrexate, Wahl et al, ; not shown). These results suggest that increased apoptosis is not the reason the buccopharyngeal membrane is failing to perforate in embryos deficient in JNK signals.…”
Section: Resultssupporting
confidence: 75%
“…Longer exposure times often lead to severe effects where tissues separated from the face (n = 10; 1 experiment; not shown) and, therefore, were not assessed. We observed similar results when embryos were treated with chemicals shown to induce cell death in Xenopus (2% ethanol, Kot‐Leibovich and Fainsod, ; and methotrexate, Wahl et al, ; not shown). These results suggest that increased apoptosis is not the reason the buccopharyngeal membrane is failing to perforate in embryos deficient in JNK signals.…”
Section: Resultssupporting
confidence: 75%
“…Although some Authors did not find any evidence to confirm a positive association between the use of folic acid supplements during pregnancy and the risk of CP or CL±P (37), further evidence to support the role of folic acid was produced by other investigators (38,39). Methylenetetrahydrofolate reductase coded by MTHFR gene is a key enzyme in folic acid metabolism.…”
Section: Supplements and Vitamins During Pregnancymentioning
confidence: 98%
“…To understand the role of folate metabolism in OFCs, the impact of folate reduction on Xenopus orofacial morphogenesis was examined alone, as well as in context of RA signaling. Using morpholino and pharmacological inhibitors targeting Dhfr, and face transplants the studies demonstrated that loss of folate metabolism can lead to alterations in the shape of the mouth and a narrower, underdeveloped face due to loss of jaw muscles and cartilages [51], a set of defects rescued by treatment with folinic acid.…”
Section: Craniofacial Disorders Modeled In Xenopusmentioning
confidence: 99%